Green Retailing Practices: An Exploratory Comparison between Chinese and British Retailers. (December 2013) - Wang, Chengbo; Li, Xiaomei; Mao, Zhaofang
Constituting the link between supply and demand, retailers can play an important role in a supply chain's green operations and logistics activities, which are one of the key contemporary concerns of governments and the general public. China, as a huge, fast-developing and opening marketplace has been attractive to British and other international retailers. However, the competition facing these retailers in the Chinese marketplace is intensifying. Research shows that British retailers began greening their business operations earlier than Chinese businesses that are still at an early stage. British retailers thus have an early-mover advantage with green operations as a characteristic competitive strength. The comparative study presented in this paper on the current green status/approaches of both Chinese and British retailers will be valuable to managers who are developing green strategies to enhance their competitiveness in the Chinese retail sector; the paper also enriches green theories in relation to this particular marketplace.